Toward a Better Understanding of Gender-Based Performance in the Obstetrics and Gynecology Clerkship. (March 2015) - Bibbo, Carolina; Bustamante, Alejandrina; Wang, Lili; Friedman, Frederick; Chen, Katherine T.
<x xml:space="preserve">Abstract</x> Purpose To better understand why women outperform men in the obstetrics and gynecology (Ob/Gyn) clerkship. Method The authors conducted a retrospective cohort study of students who rotated in the Ob/Gyn clerkship from 2008 to 2011 and graduated by May 2012 from the Icahn School of Medicine at Mount Sinai in New York City. They compared female and male students' performance on preclerkship standardized tests (the Medical College Admission Test [MCAT] and United States Medical Licensing Examination [USMLE] Step 1) and on Ob/Gyn clerkship components (clinical skills achievement, oral and written case presentations, clinical evaluations, and National Board of Medical Examiners [NBME] subject examination). Results The study included 163 (53.4%) women and 142 (46.6%) men. Among students who took the MCAT, women scored lower than men with a mean (standard deviation) of 33.2 (3.2) versus 34.6 (3.3) (P = .001). Similarly, among all students, women scored lower than men on the USMLE Step 1: 227 (19.1) versus 232.5 (18.8) (P = .012). There were no significant gender differences on most clerkship components. However, women scored higher than men on the Ob/Gyn NBME subject examination: 78.0 (7.5) versus 74.8 (8.4) (P = .001). Consequently, female students achieved higher overall clerkship scores than men: 88.5 (5.6) versus 87.1 (5.1) (P = .024). Analysis of covariance confirmed that gender is associated with NBME subject examination score (P < .001). Conclusions Women outscored men on the NBME subject examination in Ob/Gyn and thereby outperformed men in the Ob/Gyn clerkship.